Analisis Lokasi Pos Damkar Berdasarkan Peta Kerawanan Kebakaran Menggunakan SIG Di Jakarta Timur - Adhi Rangga Evalianto; Mataburu, Ilham B; Jalaludin, Muzani (Geography Education Study Program, Universitas Kanjuruhan Malang, 2024)
This research aims to analyze the range of fire post locations on the fire vulnerability map in East Jakarta. The methodology of this research is quantitative research with data analysis techniques using GIS analysis, namely network analysis to create fire post affordability, and overlay analysis to create fire vulnerability maps. Based on result there are still areas that have not been reached, especially in Duren Sawit, Cakung, Makasar, Cipayung and Ciracas Districts. When viewed in terms of fire disaster vulnerability, East Jakarta City has a medium-high level of vulnerability, while areas with a low level of vulnerability are very few with an area of only 15 hectares. Areas with a medium level of vulnerability dominate with a total area of 12,362 hectares, while areas with a high level of vulnerability cover an area of 6,124 hectares. If an overlay analysis is carried out on the distance between fire posts and the fire vulnerability of residential areas in East Jakarta, it can be seen that there are still areas with a high-medium fire vulnerability class that are not yet reached by fire posts covering an area of 6,018.08 hectares. In fact, 46% of all areas with a high level of fire vulnerability have not been reached by fire stations. These areas are found in Duren Sawit, Ciracas and Cipayung sub-districts. It is recommended that fire posts be built in unreached areas to ensure disaster management is more efficient. This research aims to analyze the range of fire post locations on the fire vulnerability map in East Jakarta. The methodology of this research is quantitative research with data analysis techniques using GIS analysis, namely network analysis to create fire post affordability, and overlay analysis to create fire vulnerability maps. Based on result there are still areas that have not been reached, especially in Duren Sawit, Cakung, Makasar, Cipayung and Ciracas Districts. When viewed in terms of fire disaster vulnerability, East Jakarta City has a medium-high level of vulnerability, while areas with a low level of vulnerability are very few with an area of only 15 hectares. Areas with a medium level of vulnerability dominate with a total area of 12,362 hectares, while areas with a high level of vulnerability cover an area of 6,124 hectares. If an overlay analysis is carried out on the distance between fire posts and the fire vulnerability of residential areas in East Jakarta, it can be seen that there are still areas with a high-medium fire vulnerability class that are not yet reached by fire posts covering an area of 6,018.08 hectares. In fact, 46% of all areas with a high level of fire vulnerability have not been reached by fire stations. These areas are found in Duren Sawit, Ciracas and Cipayung sub-districts. It is recommended that fire posts be built in unreached areas to ensure disaster management is more efficient.